2017
DOI: 10.1038/s41467-017-01962-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell absolute contact probability detection reveals chromosomes are organized by multiple low-frequency yet specific interactions

Abstract: At the kilo- to megabase pair scales, eukaryotic genomes are partitioned into self-interacting modules or topologically associated domains (TADs) that associate to form nuclear compartments. Here, we combine high-content super-resolution microscopies with state-of-the-art DNA-labeling methods to reveal the variability in the multiscale organization of the Drosophila genome. We find that association frequencies within TADs and between TAD borders are below ~10%, independently of TAD size, epigenetic state, or c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
99
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 62 publications
14
99
1
1
Order By: Relevance
“…Previous studies have reported that loci which display strong interactions in Hi-C do 201 not always equate to frequent interactions in single cells (Bonev et al, 2017;202 Fudenberg and Imakaev, 2017). Therefore we wanted to accurately quantitate the 203 frequency of polycomb chromatin domain interactions by determining the number of 204 FISH probe measures that may be considered to be in contact (Cattoni et al, 2017). 205…”
Section: Polycomb Chromatin Domain Interactions Are Disrupted By Cohementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that loci which display strong interactions in Hi-C do 201 not always equate to frequent interactions in single cells (Bonev et al, 2017;202 Fudenberg and Imakaev, 2017). Therefore we wanted to accurately quantitate the 203 frequency of polycomb chromatin domain interactions by determining the number of 204 FISH probe measures that may be considered to be in contact (Cattoni et al, 2017). 205…”
Section: Polycomb Chromatin Domain Interactions Are Disrupted By Cohementioning
confidence: 99%
“…To assess what proportion of our inter-probe distance measurements might be considered as co-incident we applied the following rationale, which is as described (Cattoni et al, 2017). To measure the error in colocalisation precision within a realistic, non-ideal experimental situation, we labelled and hybridised the same fosmid probe with both digoxygenin (detected with FITC) and Cy3 in cells, as per the experimental conditions.…”
Section: Contact Probability Threshold Calculationmentioning
confidence: 99%
“…This model would explain our observations that CTCF/cohesin sites flanking the α-globin self-interacting domain become juxtaposed around a decompacted loop of chromatin in erythroblasts. In this model, domains could arise from a dynamic balance of cohesin loading and removal and loop extrusion and blocking 26 . We have previously noted an accumulation of cohesin in erythroid cells around all five enhancer-like elements of the α-globin cluster 13 , which may act as entry points for cohesin.…”
mentioning
confidence: 99%
“…Interestingly, the behavior of the two alleles in the same nucleus is not correlated, which suggests that the variability present is largely intrinsic and not dependent on cell-level variables such as cycle stage [16]. However, energy was not considered as a variable by the authors.…”
Section: Figurementioning
confidence: 96%